(3NaI GddZI hSQ GdYQHjIs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI QSGdI LYdgG YfO Gdedc Gf jMeO Hf GSeGYjd ebOeI dcJGH abg GddZI ef COH Gddg hQShdg eMeO Udi Gddg Ydjg hSde hef CMH GdQShd GdYQHj CMH GdYQHjI GdJj HgG fRd CaVd GdcJH s
(3HChdI bQGAGJ hSeGYGJs
(3hHgG GVWQGH hJacc aj GdChQGbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3eJaQbGJs